2021
DOI: 10.29173/iasl8090
|View full text |Cite
|
Sign up to set email alerts
|

The Power and the Passion: Igniting a Love of Reading through Literature Circles

Abstract: This paper presents the simple but successful Literature Circles model at St Andrew's Cathedral School within the context of the importance of developing reading as a foundation for building knowledge. It covers crucial factors for success of the program, practicalities and procedures, the selection of books, and strategies for substantive discussion and a book list of the most successful titles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indeed, literary texts provide students with aesthetic models of learning the cultural dimensions and encourage them to use standard language e ectively. Moreover, research has indicated that reading and responding to literary texts improve students' communication and achievement and equip them with the nest examples of English usage [1]. Van [2] called for teaching literary texts intensively in EFL classrooms as they create a meaningful context for language use and sustain students' acquisition of a rich repertoire of vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, literary texts provide students with aesthetic models of learning the cultural dimensions and encourage them to use standard language e ectively. Moreover, research has indicated that reading and responding to literary texts improve students' communication and achievement and equip them with the nest examples of English usage [1]. Van [2] called for teaching literary texts intensively in EFL classrooms as they create a meaningful context for language use and sustain students' acquisition of a rich repertoire of vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…While literature has numerous functions in the education system, instructional evolution and developments in Information and Communication Technology have revolutionized its versatility and transformed the way classrooms embrace its teaching and learning. At the tertiary level, literature instruction that prepares pre-service teachers for the Teaching of English as a Second Language (TESL) can serve multiple functions like to instil the passion for reading, build aesthetic appreciation through language, foster higher-order thinking abilities, or nurture personal growth (Greef, Jenkins & Comer, 2021). To provide support for these learners, literature instruction offers not just a platform for exploring and experimenting with different literary genres for the teaching of the English language, but also exposes them to the pedagogical processes that nurture agility and resilience that are vital for developing professional attributes to become future educators (Masry & Alzaanin, 2021).…”
Section: Introductionmentioning
confidence: 99%